The Peripherin Gene Regulates the Migration of Bone Marrow Mesenchymal Stem Cells in Wuzhishan Mini Pigs - Zheng Feng; Wentong Li; Ying Xia; Hui Yu; Hua Li; Kui Li; Yulian Mu (Stem Cells International)
Increasing the migratory capacity of the implanted mesenchymal stem cells (MSCs) is a major challenge in developing successful cell transplantation therapies. Nevertheless, the regulatory factors involved in the migration of BMMSCs remain largely unknown. In this study, we studied the role of the peripherin (PRPH) gene in regulating the ability of Wuzhishan mini pig (WZSP) BMMSCs to migrate in vitro. Four different shRNA vectors directed against PRPH were designed and transfected into BMMSCs. The vector with the best interference effect was chosen to be used in the following experiments. The expression level of PRPH in BMMSCs was determined by quantitative real-time PCR and western blot analysis. The migration capacity of the BMMSCs was estimated using a scratch assay, a transwell in vitro migration model assay, and filamentous actin staining. The results showed that shRNA-mediated knockdown of the expression of the PRPH gene in BMMSCs reduced the ability of these cells to migrate. Overall, these results illustrate that the PRPH gene regulates the migration of BMMSCs in the WZSP.